Clinical Implications of Inter- and Intratumor Heterogeneity of Immune Cell Markers in Lung Cancer. (17th August 2021) - Zhao, Wei; Zhu, Bin; Hutchinson, Amy; Pesatori, Angela Cecilia; Consonni, Dario; Caporaso, Neil E; Zhang, Tongwu; Wang, Difei; Shi, Jianxin; Landi, Maria Teresa
Abstract: Background: Immune cell transcriptome signatures have been widely used to study the lung tumor microenvironment (TME). However, it is unclear to what extent the immune cell composition in the lung TME varies across histological and molecular subtypes (intertumor heterogeneity [inter-TH]) and within tumors (intratumor heterogeneity [ITH]) and whether ITH has any prognostic relevance. Methods: Using RNA sequencing in 269 tumor samples from 160 lung cancer patients, we quantified the inter-TH of immune gene expression and immune cell abundance and evaluated the association of median immune cell abundance with clinical and pathological features and overall survival. In 39 tumors with 132 multiregion samples, we also analyzed the ITH of immune cell abundance in relation to overall survival using a variance-weighted multivariate Cox model not biased by the number of samples per tumor. Results: Substantial inter-TH of 14 immune cell types was observed even within the same histological and molecular subtypes, but early stage tumors had higher lymphocyte infiltration across all tumor types. In multiregion samples, an unbiased estimate of low ITH of overall immune cell composition (hazard ratio [HR] = 0.40, 95% confidence interval [CI] = 0.21 to 0.78; P  = .007), dendritic cells (HR = 0.24, 95% CI = 0.096 to 0.58; P  = .002), and macrophages (HR = 0.50, 95% CI = 0.30 to 0.84; P  = .009) was strongly associated with poor survival. The ITH of 3 markers, including CD163 and CD68 (macrophages) and CCL13 (dendritic cells), was enough to characterize the ITH of the corresponding immune cell abundances and its association with overall survival. Conclusion: This study suggests that lack of immune cell diversity may facilitate tumor evasion and progression. ITH inferred from CCL13, CD163, and CD68 could be used as a prognostic tool in clinical practice.